2008
DOI: 10.1007/s00421-008-0793-8
|View full text |Cite
|
Sign up to set email alerts
|

Twitch potentiation after voluntary versus electrically induced isometric contractions in human knee extensor muscles

Abstract: Twitch potentiation in knee extensor (KE) muscles after a 7-s conditioning isometric maximal voluntary contraction (MVC trial), submaximal (25% MVC) voluntary contraction (SVC trial) and submaximal tetanic contraction (25% MVC) induced by percutaneous electrical stimulation at 100 Hz (PES trial) was compared in 12 men aged 19-25 years. Isometric twitch characteristics of KE muscles were measured before conditioning contraction and following 10-min recovery by supramaximal electrical stimulation of the femoral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
39
3
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 48 publications
9
39
3
8
Order By: Relevance
“…They found an enhancement of 86% in peak RTD, that is, less than what is presented in our study. For the quadriceps muscles of active subjects, peak twitch has been shown to increase by 48%, RTD by 87%, and RTR by 102% (33), that is, lesser increases of peak twitch and RTD but larger increases of RTR compared with our study. The quadriceps muscles are known to have a higher percentage of type 2 fibers compared with the triceps surae (14).…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…They found an enhancement of 86% in peak RTD, that is, less than what is presented in our study. For the quadriceps muscles of active subjects, peak twitch has been shown to increase by 48%, RTD by 87%, and RTR by 102% (33), that is, lesser increases of peak twitch and RTD but larger increases of RTR compared with our study. The quadriceps muscles are known to have a higher percentage of type 2 fibers compared with the triceps surae (14).…”
Section: Discussioncontrasting
confidence: 70%
“…Such contractions have been shown to increase the peak twitch and rate of torque development (RTD) and to decrease the time to peak (TTP) and half relaxation time (HRT) of an electrically evoked twitch in human muscles for up to 10 min (5,24,28,33). Electrically evoked twitches are used to assess muscle contractile properties because they allow for isolated studies of contractile properties, whereas the assessment of sports performance enhancement after a conditioning task can be caused by many factors, including psychological placebo-like effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few investigations have compared the extent of TP elicited after voluntary and NMES at high‐stimulation‐frequency (80–100 H Z ) conditioning contractions at equivalent target levels. 4, 14, 15 Requena et al compared the extent of TP after voluntary vs. NMES contractions at 25% of maximal voluntary contraction (MVC) torque level, and demonstrated that the extent of TP after a 7‐s NMES at 100 H Z was greater than that after a 7‐s voluntary contraction in knee extensor muscles 15. In contrast, Jubeau et al showed that a 10‐s NMES of the quadriceps femoris at 100 H Z with 40% MVC torque induced a smaller TP than a 10‐s voluntary contraction 14.…”
mentioning
confidence: 99%
“…In this context, most studies investigate the influence of PAP on lower limbs and evaluate the performance improvement through vertical jumps (12,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). However, a smaller number of studies investigated the effects of PAP on sprint performance, with results expressed at different distances (5-7, 13, 28-34).…”
Section: Introductionmentioning
confidence: 99%